Silk Fibroin Microneedle Patches for the Treatment of Insomnia - Zhenzhen Qi; Jiaxin Cao; Xiaosheng Tao; Xinyi Wu; Subhas C. Kundu; Shenzhou Lu (MDPI AG, 2021)
As a patient-friendly technology, drug-loaded microneedles can deliver drugs through the skin into the body. This system has broad application prospects and is receiving wide attention. Based on the knowledge acquired in this work, we successfully developed a melatonin-loaded microneedle prepared from proline/melatonin/silk fibroin. The engineered microneedles' morphological, physical, and chemical properties were characterized to investigate their structural transformation mechanism and transdermal drug-delivery capabilities. The results indicated that the crystal structure of silk fibroin in drug-loaded microneedles was mainly Silk I crystal structure, with a low dissolution rate and suitable swelling property. Melatonin-loaded microneedles showed high mechanical properties, and the breaking strength of a single needle was 1.2 N, which could easily be penetrated the skin. The drug release results in vitro revealed that the effective drug concentration was obtained quickly during the early delivery. The successful drug concentration was maintained through continuous release at the later stage. For in vivo experimentation, the Sprague Dawley (SD) rat model of insomnia was constructed. The outcome exhibited that the melatonin-loaded microneedle released the drug into the body through the skin and maintained a high blood concentration (over 5 ng/mL) for 4-6 h. The maximum blood concentration was above 10 ng/mL, and the peak time was 0.31 h. This system indicates that it achieved the purpose of mimicking physiological release and treating insomnia.